Nutrient intake and digestibility in sheeps fed diets with corn germ and Miúda forage cactus (Nopalea cochenillifera (Revista Ciencia Agraria, 2025)
The objective was to evaluate the effect of using corn germ and the forage cactus cv. Miúda in the diet of sheep on nutrient intake and digestibility. Four male sheep with an average initial weight of 35 kg, were used, and distributed in a Latin square experimental design. The treatments consisted of four experimental diets: without Miúda cactus (MFC) and germ (CONT); without MFC + germ (GIMEX); with MFC and without germ (MFC); with MFC and germ (MFC+GIMEX). However, a significant effect (P0.05); however, significant effects were observed for the coefficients of digestibility of organic matter (OM) (664.5 x 742.7 g kg-1 DM) and NFC (657.1 x 838.8 g kg-1 DM). The present study determined that combining corn germ with forage palm is a viable option for sheep production in northeastern Brazil in terms of diet quality and utilization.
Keywords: association; intake; digestibility; lipidic source; forage cactus